Bentuk-Bentuk Kemerosotan Akhlak Mahasiswa Di Perguruan Tinggi - Rishan, Muhamad; Azizi, Hafizul; Azura, Khairani; AlFatih, Muhammad Adrian; Firdaus, Raihan Syah (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2018)
Degradation of morals or moral decadencehas attacked young generations especially college students. Therefore, this paper aims to find out forms of moral decadence found in college students. This research uses qualitative method with case study approach, the data collected through direct interview with ten informants (college students) by using purposive sampling technique. In order to strenghten interview data, the writer performed passive participation observation by coming directly to the observed location. All results of the interview were analyzed using Milles and Haubermans pattern. The research foundÂ nine forms of moral decadence in college students. They are: i) negligent in worship, ii)sexual promiscuity, iii) involved in drug abuse, iv) hedonism, v) revealing awrah, vi) lack of ethics, vii) impolite speaking , viii) dishonest in academics and ix) lack of time management. The results of this research can be used as initial dataÂ for future research investigating similar problems in different context and issues.